The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1097/bpo.0b013e3182a11eee
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Barbed Sutures During Scoliosis Fusion Wound Closure

Abstract: Level II-therapeutic study, prospective nonrandomized cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 10 publications
3
13
0
Order By: Relevance
“…KBS was associated with a shorter time to wound closure in our study, confirming results of previous studies 20 21 23 24 . Stephens et al .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…KBS was associated with a shorter time to wound closure in our study, confirming results of previous studies 20 21 23 24 . Stephens et al .…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Mansour et al . found that KBS closure of spinal fusion incisions resulted in hospital charges for operation time that were 884.60 USD lower than those of surgeries using KTS 23 . The cost of operating room time estimates are based upon the average cost for professional staff and resources required for these cases.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Closure can often be a time consuming and considerable part of the surgery, and reducing this time has been targeted as a method of cost management. Suture type has been determined to be a factor that may influence closure time and thus costs, as well as having effect on direct material costs (2).…”
Section: Introductionmentioning
confidence: 99%
“…Barbed sutures, and those that are bidirectional in nature, were recently introduced to allow for simultaneous closure from the wound center (3). Studies have demonstrated that the use of barbed knotless sutures allows for a faster and more efficient closure with less material used, while providing a watertight arthrotomy closure (2).…”
Section: Introductionmentioning
confidence: 99%